Comprehensive Safety Assessment and Improvement Strategies for the Satdobato-Budhanilkantha Corridor in Kathmandu Valley, Nepal - Singh, Samridhi; Mehta, Utsav; Pokhrel, Asmita (International Journal on Engineering Technology and Infrastructure Development, 2025)
This study evaluates road safety conditions along Kathmandu's critical 17.7 km Satdobato-Budhanilkantha corridor, where infrastructure deficiencies contribute to high accident rates. Using GIS mapping and field surveys, we have identified severe shortcomings: only 47% of footpaths have tactile paving, 1 of 53 zebra crossings remains visible, and just 12 of 32 bus stops have proper laybys. Our findings reveal how inadequate signage, hazardous parking, and poor pedestrian facilities elevate crash risks. We propose targeted interventions including signal upgrades, crossing improvements, and optimised signage to enhance safety in this vital urban artery.